The International Society for Sexual Medicine: A Rich History and a Bright Future. Issue 2 (15th May 2013) - Lewis, Ronald W.
Abstract: Based upon physical presence at most of the historical moments of the development of the International Society for Sexual Medicine (ISSM), extensive personal records on meetings and correspondence associated with the business and the work of the International Society for Sexual and Impotence Research and the ISSM, and information provided by the business office of the ISSM, a review paper was created to present to the reader an accurate history of the ISSM. The article is divided into the early beginnings of the idea of the field of sexual medicine, followed by the organization of what was to become eventually the International Society for Sexual Medicine, description of the development of biennial meetings and some of the major events that occurred at these meetings, a description of officers and leaders of the society and some of their key contributions, other meetings that the ISSM was actively involved in in the field of sexual medicine, a detailed discussion of publications and communications of the organization, and finally a description of the involvement of the ISSM with the recognition of scientific achievement and research in the field. This history is indeed very rich and unique for the parallelism to the development of the entire field of sexual medicine as a true science. The author has spent a great deal of time in making sure that there is written material that substantiates the history that is outlined in this document. It is provided to the reader as a true historical perspective on the ISSM.Lewis RW. The International Society for Sexual Medicine: A rich history and a bright future. Sex Med Rev **;**:**–**.